2017
DOI: 10.1155/2017/3607383
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Preparation and Performance Characterization of the HMX/F2602 Microspheres by One-Step Granulation Process

Abstract: A new one-step granulation process for preparing high melting explosive-(HMX-) based PBX was developed. HMX/F 2602 microspheres were successfully prepared by using HMX and F 2602 as the main explosive and binder, respectively. The particle morphology, particle size, crystal structure, thermal stability, and impact sensitivity of the as-prepared HMX/F 2602 microspheres were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), laser particle size analyzer, differential scanning calorimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Among them, type 26 fluoroelastomer is one of the most widely used fluoroelastomers, and it is also commonly used as an adhesive for explosives. Hou et al, 14 Bian Bian et al, 15 and Ji et al 16 successfully coated F 2602 on the surface of HMX by the one-step granulation method and used the suspension spray-drying method to prepare HMX/F 2602 microspheres, which reduced the sensitivity of HMX and improved the safety performance of HMX. In this study, F 2602 / GAP/CL-20 energetic fibers were prepared by electrostatic spinning with F 2602 /GAP as the coating binder and CL-20 as the high-energy explosive.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, type 26 fluoroelastomer is one of the most widely used fluoroelastomers, and it is also commonly used as an adhesive for explosives. Hou et al, 14 Bian Bian et al, 15 and Ji et al 16 successfully coated F 2602 on the surface of HMX by the one-step granulation method and used the suspension spray-drying method to prepare HMX/F 2602 microspheres, which reduced the sensitivity of HMX and improved the safety performance of HMX. In this study, F 2602 / GAP/CL-20 energetic fibers were prepared by electrostatic spinning with F 2602 /GAP as the coating binder and CL-20 as the high-energy explosive.…”
Section: Introductionmentioning
confidence: 99%
“…At a certain heating rate, the external energy absorbed by the particles increases for a period of time, and the heated area and the reactivity increase. In addition, owing to the massive agglomeration of particles, its specific surface area and the number of atoms located on the surface increase [21,22]. Therefore, E a and the thermal decomposition temperature have decreased as compared to the raw HMX.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that the raw RDX (Figure 7a), Refined RDX (Figure 7b), RDX/MUF-1 (Figure 7c), and RDX/MUF-2 ( Figure 7d) composite energetic microspheres have similar thermal decomposition behaviors, possessing a very distinct endothermic peak at around 204 • C. That is, the addition of the MUF binder has little influence on the stability of RDX crystal form. Based on the decomposition peak temperature values of three different RDX samples at different heating rates, in order to ensure the accuracy of the calculation the decomposition activation energy E a and the pre-exponential factor A of the four RDX samples were calculated by the Kissinger formula, Ozawa formula and Starink formula, respectively [20,21]. ln( β…”
Section: Thermal Propertiesmentioning
confidence: 99%